Determining Maternal Risk Factors and Biomarkers Associated with Preterm Birth: A Multicentric Cohort Study - Vyas, Parth H; Bhimani , Parth M; Adhvaryu , Dhvani S; Popat, Nandini A; Vyas , Bhavin A (Indian Journal of Community Health, 2025)
Background: Preterm birth remains a significant public health challenge, accounting for around 75% of all neonatal deaths. Aim & Objective: To determine various risk factors along with potential biomarkers associated with preterm birth. Settings and Design: This prospective multicentric cohort study was conducted in two private hospitals in urban South Gujarat from January 2023 to June 2023. Material and Methods: Using a purposive sampling method, a total of 150 women aged 20 to 45 years were initially screened. After applying the eligibility criteria, 48 were excluded, and 102 participants were ultimately enrolled in the study. Statistical analysis used: Chi-square test was used to compare distribution of variables, univariate analysis to evaluate associations, odds ratios and 95% confidence intervals (CI) with P values were used. Results: From 102 participants, 21 (20.6%) were preterm and 81 (79.4%) were full- term. Steroid use (OR 3.28, P=0.03), history of dysmenorrhea (OR 5.26, P < 0.01), twin pregnancy (OR 14.83, P < 0.01), Individuals with an abnormal BMI were over three times more likely to experience preterm birth, and this link was found to be statistically significant (OR 3.12, P = 0.03). History of abortion had higher odds (OR 2.05). Biomarkers like Abnormal AMH (OR 3, P = 0.21), low progesterone (OR = 8.19, p < 0.01), Abnormal prolactin (OR = 8.86, p < 0.01), Abnormal ferritin (OR 36, P < 0.01) were associated with the preterm birth. Conclusions: Usage of steroids, dysmenorrhea, abnormal BMI and twin pregnancy are risk factors of preterm birth. Serum ferritin, prolactin and serum progesterone were identified as potential biomarkers which can be used to predict preterm birth and had positive association from study findings.